2016
DOI: 10.18632/oncotarget.12963
|View full text |Cite
|
Sign up to set email alerts
|

Systematic approach identifies RHOA as a potential biomarker therapeutic target for Asian gastric cancer

Abstract: Gastric cancer (GC) is a highly heterogeneous disease, in dire need of specific, biomarker-driven cancer therapies. While the accumulation of cancer "Big Data" has propelled the search for novel molecular targets for GC, its specific subpathway and cellular functions vary from patient to patient. In particular, mutations in the small GTPase gene RHOA have been identified in recent genome-wide sequencing of GC tumors. Moreover, protein overexpression of RHOA was reported in Chinese populations, while RHOA mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…Interestingly, a c-Met inhibitor significantly repressed the growth of GC cells transfected with WT-RhoA but not the mutated Y42C form of RhoA. Previously, it was shown that high levels of RhoA increased the activity of Rho GTPases and accelerated the progression of GC [29,30], whilst downregulation of RhoA suppressed GC cell growth [31]. In agreement with previous reports, we found that RhoA is elevated in GC patients and leads to poor survival.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a c-Met inhibitor significantly repressed the growth of GC cells transfected with WT-RhoA but not the mutated Y42C form of RhoA. Previously, it was shown that high levels of RhoA increased the activity of Rho GTPases and accelerated the progression of GC [29,30], whilst downregulation of RhoA suppressed GC cell growth [31]. In agreement with previous reports, we found that RhoA is elevated in GC patients and leads to poor survival.…”
Section: Discussionsupporting
confidence: 92%
“…RhoA, a member of the Rho homolog family of small GTPases, promotes the reorganization of the actin cytoskeleton and regulates cell shape, attachment and motility (26). Increased activation of RhoA has been associated with tumor cell proliferation and metastasis (27,28). In OC, the activation of RhoA GTPase and downstream ROCK led to enhanced cell invasion and migration (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent GC studies by our group (Chang et al, 2016a;Nam et al, 2014) indicated that WNT5A significantly associated with GC prognosis; we also demonstrated the feasibility of therapeutically targeting WNT signalling (Chang et al, 2016b). In addition, Notch signalling, a well-known cancer hallmark (Hanahan and Weinberg, 2011), also represents a new, promising therapeutic target in GC (Yao et al, 2017), and DNA mutations have been intimately associated with DNA repair pathways (Hanahan and Weinberg, 2011).…”
Section: Introductionmentioning
confidence: 60%